2018
DOI: 10.1007/s10157-018-1593-z
|View full text |Cite
|
Sign up to set email alerts
|

Decreased KLHL3 expression is involved in the pathogenesis of pseudohypoaldosteronism type II caused by cullin 3 mutation in vivo

Abstract: KLHL3 expression was decreased in CUL3 mice. However, expression levels of other KLHL family proteins were comparable between the wild-type and mutant mice. These findings indicate that the decreased abundance of KLHL3 is a specific phenomenon caused by mutant CUL3 (Δexon9). Our findings would improve our understanding of the pathogenesis of PHAII caused by CUL3 mutation in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 35 publications
5
31
0
Order By: Relevance
“…53 Furthermore, CUL3D9 showed a similar effect on the substrate adaptors, both in vitro 36,37 and in vivo. 42 Because CUL3D9 also has an impaired interaction with the CSN, the results are consistent with decreased CSN activity as a partial mechanism for the disease. Additionally, the selectiveness of CSN inactivation to decrease KLHL3 but not Keap1 abundance may explain why the disease phenotype is only observed in the kidney and smooth muscle.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…53 Furthermore, CUL3D9 showed a similar effect on the substrate adaptors, both in vitro 36,37 and in vivo. 42 Because CUL3D9 also has an impaired interaction with the CSN, the results are consistent with decreased CSN activity as a partial mechanism for the disease. Additionally, the selectiveness of CSN inactivation to decrease KLHL3 but not Keap1 abundance may explain why the disease phenotype is only observed in the kidney and smooth muscle.…”
Section: Discussionsupporting
confidence: 58%
“…37 Although this hypothesis has proved controversial, 11 genetic deletion of KLHL3 does lead to a mouse phenotype that resembles FHHt, 41 and recent results confirm that low KLHL3 abundance in mice carrying the pathogenic CUL3D9 mutation contributes to the phenotype. 42 Here, we tested the hypothesis that defective CSN action contributes to the FHHt phenotype mice by deleting a component of the key enzyme involved in removing NEDD8 from the cullin proteins. The results confirm a role for deficient deneddylation for the disease process, but also provide novel insight into factors regulating NCC abundance, in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…KLHL3 destruction was prevented by the neddylation inhibitor MLN4924, sug-gesting that the altered function of CUL3⌬9 was from hyperneddylation. These findings were confirmed by us and others (10,13,28,39) and suggested that KLHL3 degradation contributes to WNK4 accumulation. Schumacher et al (28) further demonstrated impaired CSN activity toward CUL3⌬9 by showing that the mutation had a decreased rate of deneddylation.…”
Section: Csn Binding and Activity Toward Cul3⌬9 Is Disruptedsupporting
confidence: 82%
“…Meanwhile, kelch-like3 (KLHL3) promotes substrate ubiquitination of bound proteins via interactions of the BTB domain with the cullin 3 component of a cullin-RING E3 ubiquitin ligase complex [43]. Yoshida et al [44] further demonstrated that mice which present a pseudohypoaldosteronism type II (PHA II) phenotype (i.e., a hereditary hypertensive disease) exhibit a significant decrease in KLHL3 expression in both kidney and brain tissues, thereby indicating that KLHL3 may contribute to hereditary hypertension. Since hypertension is an important risk factor for aneurysm rupture, abnormal expression of KLHL3 may be associated with the onset and rupture of IAs.…”
Section: Categorymentioning
confidence: 99%